2022
DOI: 10.1186/s12915-022-01327-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of eigenvectors provides genetic insights into selective breeding for tomato metabolites

Abstract: Background Long-term domestication and intensive breeding of crop plants aim to establish traits desirable for human needs, and characteristics related to yield, disease resistance, and postharvest storage have traditionally received considerable attention. These processes have led also to negative consequences, as is the case of loss of variants controlling fruit quality, for instance in tomato. Tomato fruit quality is directly associated to metabolite content profiles; however, a full underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
0
3
0
1
Order By: Relevance
“…We used three strategies to identify the selected genomic regions, including EigenGWAS, nucleotide diversity (π) analysis, and XP-CLR methods. For EigenGWAS analysis [ 46 , 47 ], we used the first eigenvector of the Principal Component Analysis (PCA) as “phenotype” and performed GWAS on all tomato accessions using TASSEL software (version 5) [ 48 ] with the default parameters. The top 5% (6.398) windows were determined as candidate selected regions.…”
Section: Methodsmentioning
confidence: 99%
“…We used three strategies to identify the selected genomic regions, including EigenGWAS, nucleotide diversity (π) analysis, and XP-CLR methods. For EigenGWAS analysis [ 46 , 47 ], we used the first eigenvector of the Principal Component Analysis (PCA) as “phenotype” and performed GWAS on all tomato accessions using TASSEL software (version 5) [ 48 ] with the default parameters. The top 5% (6.398) windows were determined as candidate selected regions.…”
Section: Methodsmentioning
confidence: 99%
“…Such insights shed light on how genetic variances contribute to the observable characteristics of plants. Yang et al employed an Eigen Genome-Wide Association Study (EigenGWAS) methodology on a collection of 331 tomato varieties to uncover critical genetic determinants that affect metabolite variation throughout the tomato's domestication and enhancement processes, thereby emphasizing the significance of polygenic selection in the developing of tomatoes with superior fruit quality (Yang et al, 2022).…”
Section: Unraveling Plant Phenotypesmentioning
confidence: 99%
“…Kim et al (2021) identified QTL for eight fruit traits in cultivated tomatoes through a genome-wide association study based on 34,550 confident SNPs from the 51 K Axiom® tomato array. Yang et al (2022) investigated a genomewide association study of eigenvectors indicating genetic insights into selective breeding for tomato metabolites in 331 accessions. They identified two independent gene sets of fruit metabolites and 57 candidate genes related to polyphenol and polyamine biosynthesis.…”
Section: Genome-wide Association Studies (Gwas)mentioning
confidence: 99%